Contextual Factors and Motor Skills in Indigenous Amazon Forest and Urban Indigenous Children - Duarte, Marcelo Gonçalves; Valentini, Nadia Cristina; Nobre, Glauber Carvalho; Benda, Rodolfo Novellino (Frontiers in Public Health, 2022)
This study investigated the contextual factors, the motor performance and body mass index across Indigenous Land Children, Indigenous-Urban Children and Non-Indigenous Urban Children. 153 children, both sexes (71 girls, 46.4 %), from 8-to 10-years-old were assessed. The Test of Motor Gross Development – 3 was utilized. Indigenous Land Children showed higher motor performance (² = 0.37 and ² = 0.19 locomotor and object control, respectively) than Indigenous-Urban Children (p < 0.03) and non-indigenous urban children (p < 0.01); Indigenous-Urban Children showed higher motor performance than Non-Indigenous-Urban children (p < 0.01). Body Mass Index was similar across groups (² = 0,02; p = 0.15). Motor performance of Indigenous Land Children were explained by contextual factors that leads to a more active lifestyle, unsupervised free time and play outside. Urban areas, behavior was similar, and although indigenous-urban children kept some play tradition, it was not strong enough to be a protective factor for motor performance.